Abdominal cavity simulator for skill progression in videolaparoscopic sutures in Brazil - Ferreira Filho,Francisco (2018)
Abstract Purpose: To develop and test a model of teaching by means of an abdominal cavity simulator. Methods: This study had two stages: development of a teaching model and an experimental prospective study that aimed to evaluate the residents’ competence. The participants were divided into 3 groups: first-year resident, second-year resident, and senior surgeon. The two groups of resident physicians received training in the simulator, under instructor supervision for skill acquisition, according to the model proposed in first stage. The surgeons did not receive this intervention. The correlations and associations were verified through simple and multiple linear regressions. The learning curves were analysed using Cox regression models. The impact of the epidemiological characteristics was tested. Results: All residents reached the maximum score at the end of 16 steps and were comparable to the experimental (p<0.001). Conclusion: Residents who underwent training using the methodology of the proposed teaching model, which is based on realistic simulation, acquired proficiency in the accomplishment of endosutures in up to 16 hours of training in the laboratory.